A framework for efficient wastewater treatment and recycling systems - Mekala, Gayathri Devi; Davidson, B.; Samad, Madar; Boland, A.M. (International Water Management Institute, 2008)
Use of un-treated/partially treated wastewater for irrigation in the dry countries of Asia and Africa and recycling of treated wastewater in the water scarce developed countries has become a common practice due to various reasons. While the lack of wastewater treatment to appropriate levels before use is a major problem in developing countries, the high cost of wastewater recycling is the major problem in developed countries. The current paper is part of a doctoral research and presents the conceptual framework for the research and the methodology that can be used to tackle the problems associated with wastewater recycling.